Atraumatic Restorative Treatment (ART): A Three-year Clinical Study in Malawi-Comparison of Conventional Amalgam and ART Restorations - Sonja M. Kalf-Scholte, DDS; Willem E. van Amerongen, DDS, PhD; Albert J. E. Smith, DDS, MPH; (Blackwell Synergy, 2003)
This study compares the quality of class I restorations made with the atraumatic restorative treatment (ART) technique and conventional class I amalgam restorations.